Exploring new health markets: experiences from informal providers of transport for maternal health services in Eastern Uganda - Bloom Gerald; Lucas Henry; Serwadda David; Peters David H; Ssengooba Freddie; Okui Olico; Mayora Chrispus; Pariyo George W; Rahman M; Ekirapa-Kiracho Elizabeth (BMC, 2011)
Abstract Background Although a number of intermediate transport initiatives have been used in some developing countries, available evidence reveals a dearth of local knowledge on the effect of these rural informal transport mechanisms on access to maternal health care services, the cost of implementing such schemes and their scalability. This paper, attempts to provide insights into the functioning of the informal transport markets in facilitating access to maternal health care. It also demonstrates the role that higher institutions of learning can play in designing projects that can increase the utilization of maternal health services. Objectives To explore the use of intermediate transport mechanisms to improve access to maternal health services, with emphasis on the benefits and unintended consequences of the transport scheme, as well as challenges in the implementation of the scheme. Methods This paper is based on the pilot phase to inform a quasi experimental study aimed at increasing access to maternal health services using demand and supply side incentives. The data collection for this paper included qualitative and quantitative methods that included focus group interviews, review of project documents and facility level data. Results There was a marked increase in attendance of antenatal, and delivery care services, with the contracted transporters playing a leading role in mobilizing mothers to attend services. The project also had economic spill-over effects to the transport providers, their families and community generally. However, some challenges were faced including difficulty in setting prices for paying transporters, and poor enforcement of existing traffic regulations. Conclusions and implications The findings indicate that locally existing resources such as motorcycle riders, also known as "boda boda" can be used innovatively to reduce challenges caused by geographical inaccessibility and a poor transport network with resultant increases in the utilization of maternal health services. However, care must be taken to mobilize the resources needed and to ensure that there is enforcement of laws that will ensure the safety of clients and the transport providers themselves.